Superparamagnetic Nano-Biocomposites for Application as Dielectric Resonator Antennas - Casagrande-Denardin, J (Elsevier Ltd, 2017)
There is a growing global interest for the development of green technologies that allow the use of products with less damage to environment, as well as for maximum and sustainable use of natural resources. The main aim of this study was to develop superparamagnetic nano-biocomposites for application as dielectric resonator antennas, from a combination of a cardanol-based thermoset plastic, chemically modified sponge gourd fibers (NaOH 10% and NaClO 1 wt%), and magnetite nanoparticles in different contents (1, 5, and 10 wt%). The magnetite particles exhibited nanometric size, high purity and crystallinity, and superparamagnetic character. All nano-biocomposites showed superparamagnetic behavior, excellent thermal stability, good biodegradation rates, and better mechanical strength for the material with magnetite 10 wt%. All dielectric resonator antennas showed satisfactory return loss and suitability for technological applications, especially for performance in broadband. © 2016 Elsevier B.V.